Signs of the Uniqueness of the Ukrainian Printed Book in the Context of the Global Digitalisation of Art - Вікторія Олійник (Культура і мистецтво у сучасному світі)
The aim of the article is to explore the features of the uniqueness of a classic printed book as a valuable source of art studies analysis against the backdrop of dynamic transformations in Ukrainian book design. The article seeks to determine the prospects for its development as an artistic and project form, and ways to preserve the relevant design traditions. Results. The perception of traditional printed books in Ukraine today has changed in the context of the global digitisation of art. In this regard, the following opposing positions of scholars are highlighted: some predict a new phase of life for printed books, which involves the transformation of their socio-cultural role and the acquisition of different artistic content, while others underestimate the potential of traditional paper publications compared to innovative electronic formats. However, it is worth noting that the modern Ukrainian printed book has exclusive visual and aesthetic characteristics, demonstrating a unique synthesis of subject-spatial and artistic-design solutions. These characteristics include the long-term preservation of book design traditions, presentation of the designer's own artistic style (illustrator), tactile features (paper type, frame type, etc.), as well as the consistency of the layout at all levels of its implementation. The article proves this fact by comparing the design features of classic book editions with their alternative forms: electronic (multimedia) and interactive editions, as well as art books. The scientific novelty of the article consists in a comprehensive examination of the coexistence of various book forms on the modern domestic book market, their mutual influence, and the formulation of prospects for the development of the Ukrainian traditional printed books based on theoretical and empirical research of relevant sources, which was carried out for the first time. Conclusions. The article demonstrates that the highest potential of a traditional printed book lies in its highly differentiated design, unique artistic, genre and functional characteristics. The guarantee of the future of such publications is the mandatory presence of artistic and creative components in the book ensemble, as well as a genre-functional variable component.